THE IMPACT OF COLLABORATIVE WRITING STRATEGY AT STUDENTS’ WRITING SKILL IN DESCRIPTIVE TEXT - Saeful Arifin; Choiril Anwar (Universitas Muria Kudus, 2018)
The aim of this study was to find out whether or not collaborative writing strategy is effective to improve students’ writing skill in descriptive text when they were applied to the tenth grade students of SMA N 1 Karangtengah in academic year of 2015/2016. The collaborative writing strategy was the independent variable, while students’ writing skill in descriptive text was the dependent variable. Quasi experimental research design was used in this study. The population of this study was the tenth graders of SMA N 1 Karangtengah in the academic year of 2015/2016 which the total number of students was 340. The sample of this study consisted of X MIA 3 as an experimental class and X MIA 4 as a control group. The technique used in collecting the data was test. The finding of the study showed that the pre-test mean score of experimental group was 69.38 and control group was 68.71. After being given treatment for four meetings, it was found that the mean scores of experimental group was 82.15 and control group was 76.32. The result of the analysis showed that there was a significant difference between the mean score of pre-test and post-test. It was supported by t-test result in which the significant difference in the result of post-test between experimental and control group was 0.000 (smaller than 0.05). It means that Ho was rejected and Ha was accepted. Therefore, it could be concluded that collaborative writing strategy were effective to improve students’s writing skill in descriptive text.